Dignity and attitudes to aging: A cross-sectional study of older adults - Kisvetrová, Helena; Mandysová, Petra; Tomanová, Jitka; Steven, Alison (Nursing ethics, 2022)
BACKGROUND: Dignity is a multidimensional construct that includes perception, knowledge, and emotions related to competence or respect. Attitudes to aging are a comprehensive personal view of the experience of aging over the course of life, which can be influenced by various factors, such as the levels of health and self-sufficiency and social, psychological, or demographic factors. AIM: The purpose of this study was to explore the attitudes to aging of home-dwelling and inpatient older adults, and whether dignity and other selected factors belong among the predictors influencing attitudes to aging in these two different groups of older adults. RESEARCH DESIGN: Cross-sectional study using a set of questionnaires: Patient Dignity Inventory, Attitudes to Aging Questionnaire, and Barthel Index. Pearson and Spearman correlation analyses and multivariable linear regression were used for statistical processing. PARTICIPANTS AND RESEARCH CONTEXT: 233 inpatients and 237 home-dwelling older adults participated in the research in two regions of the Czech Republic. ETHICAL CONSIDERATIONS: Institutional Review Board approval was received from the authors' university. FINDINGS: The inpatients had more negative attitudes to aging (M = 74.9±10.9; P <0.0001). The predictors of their attitudes to aging were gender and dignity. Women (β = -2.969, P = 0.045) and inpatients with poor dignity ratings (β = -0.332, P <0.0001) had more negative attitudes to aging. The predictors for home-dwelling older adults were education, living arrangement, and dignity. More negative attitudes to aging were found in older adults with lower levels of education (β = 2.716, P = 0.007) who lived alone (β = 2.163, P = 0.046) and rated their dignity as low (β = -0.325, P <0.0001). DISCUSSION AND CONCLUSIONS: The results of this study add to the understanding that a sense of dignity is an important predictor of attitudes to aging for both home-dwelling older adults and inpatients.
Keywords: Aging; uznání; Attitude; lidé; průzkumy a dotazníky; senioři; Female; postoj; Cross-Sectional Studies; Aged; Surveys and Questionnaires; Respect; stárnutí; ženské pohlaví; průřezové studie; Humans